Balancing the performance benefits and health costs of leader high performance expectations: the role of servant leadership - Wang, Zhen; Chen, Huan (Employee relations, 2024)
PurposeLeader high performance expectation (LHPE) as a performance management practice is becoming more common in today’s business environment, with managers setting ambitious goals to motivate employees to excel at their jobs. This study aims to critically examine LHPE as a performance management practice within contemporary organizations, focusing on whether LHPE has opposing effects on employee performance and health, as well as how servant leadership can improve the benefits of LHPE while lowering its costs.Design/methodology/approachA path analysis of data from a three-wave survey of 416 full-time employees was used to test our hypotheses.FindingsLHPE has opposing effects on employees via two distinct pathways: motivational effects on employee performance via harmonious work passion and strain effects on employee health via work strain. In the face of LHPE, servant leadership can assist in achieving a mutual gain between employee performance and health.Originality/valueThis study contributes uniquely to the field of employee relations by offering a comprehensive analysis of LHPE’s dual effects. It moves beyond traditional views that focus on singular outcomes, providing a deeper understanding of how LHPE can both motivate and strain employees. Highlighting servant leadership’s role signifies a novel approach to managing LHPE’s complexities, presenting valuable insights for HR practitioners and organizational leaders. This research underlines the importance of balancing performance expectations with employee well-being, aligning with modern perspectives on positive employment relationships.